The 2008 Carl Ludwig Lecture: retrotrapezoid nucleus, CO(2) homeostasis, and breathing automaticity - Guyenet, Patrice G. (American Physiological Society, 2008)
The retrotrapezoid nucleus (RTN) contains 2,000 glutamatergic neurons that innervate selectively the respiratory centers of the pontomedullary region. These cells are at the ventral medullary surface in a previously identified chemosensitive region. RTN neurons are highly sensitive to acid in vitro and vigorously activated by inputs from the carotid body and from the hypothalamus in vivo. Mutations of the transcription factor Phox2b cause the congenital hypoventilation syndrome (CCHS), a disease characterized by extremely reduced chemoreflexes and the loss of breathing automaticity during sleep. RTN neurons express Phox2b and develop poorly in a mouse model of CCHS, which lacks chemoreflexes. Based on these and other data, I propose that the RTN is a critical nodal point for the homeostatic regulation of arterial Pco(2) and that the nucleus operates as follows. RTN always contributes a major fraction of the tonic excitatory drive to the respiratory centers. RTN neurons derive their activity from two sources: a chemosensory drive (intrinsic chemosensitivity and inputs from the carotid bodies) and synaptic inputs from higher brain centers (non-chemosensory drive). Under anesthesia or non-rapid eye movement sleep, the chemosensory drive to RTN neurons dominates, and, under these circumstances, the excitatory input from RTN to the respiratory controller is required for breathing automaticity. During waking and exercise, RTN contributes a reduced fraction of the total excitatory drive to the respiratory controller, but this fraction remains essential for CO(2) homeostasis because of its exquisite chemosensitivity. The working hypothesis could explain the breathing deficits experienced by CCHS patients.